Conference: Sudan’s two years of crisis—impact and pathways to recovery and resilience - Rakhy, Tarig Alhaj; Mohamed, Shima; Siddig, Khalid; Abushama, Hala; Kirui, Oliver K.; Dorosh, Paul A. (International Food Policy Research Institute, 2025)
Sudan has now entered its third year of armed conflict, resulting in economic collapse and a deepening humanitarian crisis. As of April 2025, over 8.6 million people have been internally displaced, and over 3 million have fled to neighboring countries. Famine has been confirmed in 10 areas and internally displaced person (IDP) camps, with 17 others at risk. GDP contracted by 20% in 2023 and 15% in 2024 alongside soaring inflation and widespread food insecurity. The conflict is now among the world’s worst humanitarian crises.